Pengaruh Flexible Working Arrangements, Supervisor Support dan Job Crafting terhadap Innovative Behavior Pekerja Sektor Ekonomi Kreatif - Wijayati, Suci; Pusparini, Elok Savitri (Jurnal Samudra Ekonomi dan Bisnis, 2024)
One of the characteristics of creative economy workers is innovative behavior, which is expected to continue to develop and spread among human resources in Indonesia. This research aims to provide an understanding of the factors that can encourage innovative work behavior among creative economy workers. Dominated by workers of productive age, one of the factors that can attract workers is flexibility of working hours which can produce job satisfaction and is closely related to superior support and the ability of workers to complete work under current conditions. This quantitative research involved a sample of 320 workers in the creative economy sector in Indonesia. Data was collected through questionnaires distributed online, and the relationships between variables were analyzed using CB-SEM with LISREL. The results show that flexible working arrangements, supervisor support, and job crafting have a significant influence on innovative work behavior, mediated by job satisfaction.